Diagnóstico de salud bucodental y factores de riesgo en el Colegio Nacional Mixto Manuel Benjamin Carrión de la parroquia Yangana del cantón Loja año 2013. - León Aucapiña, Shirley Viviana (2013)
Oral diseases, including dental caries, periodontal disease and malocclusion because of their frequency, local discomfort and aesthetic impact on the overall health cause, justifying their attention as a public health problem. Given this, we conducted a study of quantitative, descriptive and prospective, whose aim was to make the diagnosis of oral health and risk factors in the National Joint College "Manuel Benjamín Carrión ", parish Loja Canton Yangana 2013, examining to 131 young people, gathering information through dental and medical history survey. The results were : 96.9 % dental caries , gingival inflammation and bleeding 57.3 % , 2.3% gingival recession , bad occlusion in permanent dentition was greater prevailed class I crowded into a 44.3 % risk factors were brushed 90.1 % incorrect , visit your dentist once a year 39.7% , consumption of cariogenic food more than twice a day with a 51.1 %. The prevalence of certain diseases indicates that the study population pays little attention to oral health care, adhering to ignorance of how to maintain it. Keywords: caries risk factors, gingival inflammation bad occlusion.